A study to Chinese domestic luxury visual brand logo: From domestic to global - Wang, Zheng; Louis Ringah, Kanyan; Musdi, Shanat (FTS Scientific Publishing, 2024)
The present study examines the logotypes of successful Chinese domestic luxury brands (CDLBs), Shanghai Tang and Shang Xia, in order to reveal the underlying resonance between Chinese values and aesthetics. Based on signaling theory, the research underscores the importance of incorporating Chinese cultural elements into the branding strategies of CDLBs to attract Chinese consumers and distinguish themselves within the luxury fashion industry. The study employs a mixed-methods approach, comprising literature review, case analysis, and in-depth interviews, to analyze data from three distinct perspectives: contemporary trends, Chinese name selection, and the incorporation of local cultural elements in design. The findings suggest that CDLBs must strike a balance between conforming to current trends, particularly simplicity, and preserving authenticity, when selecting a Chinese name that holds cultural significance, and integrating traditional design elements in the details. This research provides practical guidance for professionals in the field and paves the way for future studies to explore related topics.